2010
DOI: 10.1007/s10509-010-0503-y
|View full text |Cite
|
Sign up to set email alerts
|

A class of regular and well behaved relativistic super-dense star models

Abstract: We obtain a new class of charged super-dense star models after prescribing particular forms of the metric potential g 44 and electric intensity. The metric describing the superdense stars joins smoothly with the ReissnerNordstrom metric at the pressure free boundary. The interior of the stars possess there energy density, pressure, pressuredensity ratio and velocity of sound to be monotonically decreasing towards the pressure free interface. In view of the surface density 2 × 10 14 g/cm 3 , the heaviest star o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
38
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 18 publications
0
38
0
Order By: Relevance
“…Though the Schwarzschild constant density solution is physically unrealistic, the charged analogs, obtained in [56,[102][103][104], and the charged analog of the Matese and Whitman solution, obtained in [105], may be relevant in the description of self-bound electrically charged strange quark stars. Charged analogs of the Tolman IV and VII models [106][107][108]), as the neutral ones, exhibit the physical features required for the construction of a physically realizable relativistic compact stellar structure. The charged analogs of the Vaidya-Tikekar models have been derived in [109,110].…”
Section: Introductionmentioning
confidence: 99%
“…Though the Schwarzschild constant density solution is physically unrealistic, the charged analogs, obtained in [56,[102][103][104], and the charged analog of the Matese and Whitman solution, obtained in [105], may be relevant in the description of self-bound electrically charged strange quark stars. Charged analogs of the Tolman IV and VII models [106][107][108]), as the neutral ones, exhibit the physical features required for the construction of a physically realizable relativistic compact stellar structure. The charged analogs of the Vaidya-Tikekar models have been derived in [109,110].…”
Section: Introductionmentioning
confidence: 99%
“…g 44 = B(1 + Cr 2 ) n for every integral value of n (neutral analogue of such solutions are already published by Gupta 2011a, 2011b). The charged fluid models for some integral value of n have already derived by Pant et al (2010Pant et al ( , 2011a for n = 3, Pant (2011) for n = 4, Gupta and Maurya (2011) for n = 5, Gupta (2011a, 2011b) for n = 6, and Pant et al (2011b) for n = 1, 2 and 7.…”
mentioning
confidence: 98%
“…It has been shown that presence of electromagnetic field influences the values of redshift, luminosities and maximum mass of CO [2,3]. Gupta and Maurya [4,5] found regular and well behaved charged models of super-dense star for particular choice of metric potential g 44 and electric field intensity. Pant et al [6] shown that a charged solution possess positively finite pressure and density at the center which fulfill the casuality condition, i.e., d P r dρ ≤ 1.…”
Section: Introductionmentioning
confidence: 99%